V. I. Lenin’s “Materialism and Empiriocriticism” and Natural Sciences - Grigonis, Jonas (Problemos, 1969)
The paper notes that the greatest discoveries in the late 19th and early 20th centuries were of the utmost importance for science. These discoveries resulted in the collapse of old metaphysical conceptions about the Universe and the rejection of obsolete theories. This made some scientists and a number of philosophers arrive at idealistic conclusions. The article features the role V. I. Lenin played in defeating idealistic assertions and his brilliant foresight concerning the inexhaustibility of matter. The role of V. I. Lenin’s theses in the struggle against the “physical” idealism is given due place in the article, it being noted that the book’s adherence to Party principles and the struggle for purity of Marxism are exemplary in the present-day ideological struggle against the right and the left revisionism.